An assessment of optic nerve parameters in Malay normal tension glaucoma and Primary open angle glaucoma patients - Rahim, Adlina Abdul (2012)
The recent availability of retinal imaging device plays an important role to differentiate the appearance of optic nerve in normal tension glaucoma (NTG) and primary open angle glaucoma (POAG) patients. There no published literature of these two group of glaucoma in patients of Malay ethnicity, or even those who are living in South East Asian areas. To compare optic nerve head parameters among Malay NTG and POAG patients using HR.T III analysis. A comparative cross sectional study was carried out from November 2010 till February 2012 in two hospitals with availability of glaucoma service. A total of 154 eyes of 154 Malay patients were included in this study; 32 NTG patients, 45 POAG patients and 77 control group. All participants underwent a thorough ocular examination including visual acuity, subjective refraction, anterior segment and fundus examinations, Humphrey visual field 24-2, intraocular pressure measurement, gonioscopy examination and fundus photography. An assessment of optic nerve head parameters was conducted using FIRT III by an identified masked investigator in each hospital. Comparison of these two glaucoma groups was further analyzed according to the appearance on cup disc ratio on clinical assessment and AGIS scoring system. Both glaucoma groups had notably larger discs, larger cupping, smaller retinal rims area and thinner nerve fiber layers when compared to the control group (p<0.05). NTG patients revealed larger disc and cup areas when compared to the POAG patients (the mean (SD) for disc area was 2.65 (0.41) mm2 NTG group, and 2.40 (0.36) mm2 in POAG group, p = 0.006; the mean cup area (SD) of NTG patients was 1.54 (0.43) mm2 and 1.32 (0.40) mm2 in POAG group, p = 0.027). This observation was also parallel when they were further analyzed according to the severity of glaucoma in both studied groups. The optic nerve head parameters are significantly different in Malay NTG and POAG patients when compared to healthy individuals. Disc and cup areas are significantly larger in Malay NTG compared to POAG patients, while the other parameters are comparable in both groups.